1999
DOI: 10.1177/073490419901700306
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy of Dicyandiamide-Crosslinked Epoxy Resins Containing Phenolphthalein Structures and/or a Phosphorus- Containing Additive

Abstract: The feasibility of producing halogen-free epoxy moldings having a UL-94 V-0 flammability rating has been further supported. We have shown that the fire retarding properties (OI and UL-94) of the cured epoxy were strongly im proved by using the commercial additive resorcinol bis(diphenyl phosphate) (FYROLFLEX RDP) but not improved merely by reacting phenolphthalein into the resin as a chain extender. However, a combination of the phosphate with the phenolphthalein as a chain extender gave substantially enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Liu et al 91 showed that the fire‐retarding properties (OI and UL‐94) of a cured epoxy were strongly improved by using the commercial additive resorcinol bis(diphenyl phosphate) (RDP). Moreover, a combination of the phosphate with phenolphthalein, used as a chain extender, gave substantially enhanced flame‐retardant results.…”
Section: Flame‐retardant Epoxiesmentioning
confidence: 99%
“…Liu et al 91 showed that the fire‐retarding properties (OI and UL‐94) of a cured epoxy were strongly improved by using the commercial additive resorcinol bis(diphenyl phosphate) (RDP). Moreover, a combination of the phosphate with phenolphthalein, used as a chain extender, gave substantially enhanced flame‐retardant results.…”
Section: Flame‐retardant Epoxiesmentioning
confidence: 99%
“…The control composite laminate had T g at 205°C, which is lowered in the presence of flame retardants. This may be due to plasticizing effect of FR additives in the resin 30. The higher T g values of the control C1 composite may also be due to slightly higher resin content (Table 6) and hence, higher number of sulphone groups which affect the toughening of the resin31 compared to samples C2 and C3, where resin content is lowered due to additional FR chemicals presence.…”
Section: Resultsmentioning
confidence: 96%
“…The slope of THR curve can be assumed as representative of fire spread. 17 From Figure 3, the THR of samples with Fe-OMT is decreased with increasing contents of Fe-OMT. It is very clear that the flame spread of samples with IFR and Fe-OMT decreases, and the flame spread of EP-3 is comparatively the lowest among all samples.…”
Section: Cone Calorimeter Testmentioning
confidence: 91%
“…Several approaches for modification of the EP backbone to enhance the thermal properties of EP resins have been reported. [14][15][16][17] Flame retardants such as tetrabromobisphenol-A, phosphorus-halogen mixtures, ammonium phosphate, and organophosphorus compounds have been used to impart flame retardancy to EP resins. [18][19][20][21] In a fire, halogens (such as bromine or chlorine) lead to problems of smoke and possibly enhanced toxicity and corrosion.…”
Section: Introductionmentioning
confidence: 99%